Subdecadal-scale vegetation responses to a previously unknown late-Allerød climate fluctuation and Younger Dryas cooling at Lake Meerfelder Maar (Germany) - Engels, Stefan; Brauer, Achim; Buddelmeijer, Nico; Martín-Puertas, Celia; Rach, Oliver; Sachse, Dirk; van Geel, Bas (Wiley, 2016)
Lake Meerfelder Maar (MFM) is the northernmost W European sediment record with annual laminations across the Younger Dryas (YD), and the onset of the YD in the record of MFM has previously been defined as an increase in non-arboreal pollen abundance at ca 12,680 varve a BP. Here we present a palynological record at unprecedented subdecadal-resolution for MFM, covering the Allerød-YD transition. Our results show a fluctuation in pollen accumulation rates(PAR) prior to the onset of the YD, with lower PAR between ca 12,725 and 12,685 varve a BP. The fluctuation in PAR occurs simultaneous with a previously undescribed short fluctuation in sediment composition and varve thickness, as well as with changes in biogeochemical proxies. The combined evidence indicates signs of climatic instability ca. 45 years before the onset of the YD. The PAR records of Betula and Pinus furthermore show earlier and more abrupt changes at the onset of the YD than the percentage-records do. Finally, heliophilous herbaceous taxa show a delayed increase following the onset of the YD of ca. 145 years. This paper illustrates the potential to identify previously unrecognised climate variability and vegetation change when using subdecadal resolution analyses.